ANALISIS PLATFORM CROWDFUNDING: PERSPEKTIF DARI KASUS DIGITAL MARKETING OLEH SELFLESS SCHOOL - Zaini, Firda Arum (APPS Publications, 2022)
This study aims to cover the business process area of Selfless School to analyze the problems of the difficulty to enter an existing market with strong competition. For this reason, this study provides several solutions in the form of frameworks and analysis that can be used by Selfless School. There will be several sections which are methods of data collection and marketing analysis: secondary data regarding the amount of investment, cash flow projection, and also the start-up projection in the range of 5 years. Being a new established start-up in a competitive market, Selfless School needs to appeal to a unique image and create different value from other competitors. This study provides analysis from the beginning and the current progress that cause slow profitability by using several marketing analysis methods such as blue ocean strategy, lean start-up strategy and business level strategy.